2018
DOI: 10.21897/rmvz.1481
|View full text |Cite
|
Sign up to set email alerts
|

Distribución espacial y evaluación de la contaminación ambiental por mercurio en la región de la Mojana, Colombia

Abstract: Objetivo. Se evaluó la distribución de mercurio total (HgT) en sedimentos superficiales, peces, cabello, plantas de arroz y macrofitas, como también el índice de geoacumulación por HgT en sedimentos y el potencial de riesgo por consumo de pescado en diferentes municipios afectados por actividades de minería aurífera que se han desarrollado alrededor en la región de la Mojana, Colombia. Materiales y métodos. La concentración de HgT se determinó mediante descomposición térmica, utilizando un analizador directo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…These results are in line with the IRCA value of a 100 obtained in the municipality of Mahates [38], which also uses the Canal del Dique as a source of drinking water. Mercury is accumulated through the Magdalena River basin upstream due to gold mining within the watershed [27,39].…”
Section: Resultsmentioning
confidence: 99%
“…These results are in line with the IRCA value of a 100 obtained in the municipality of Mahates [38], which also uses the Canal del Dique as a source of drinking water. Mercury is accumulated through the Magdalena River basin upstream due to gold mining within the watershed [27,39].…”
Section: Resultsmentioning
confidence: 99%
“…Fish consumption in the riparian and coastal areas of Colombia is considerably high, representing a large proportion of the animal protein consumed (DNP, 2012). In turn, various studies have reported high levels of Hg contamination in fish from these areas, especially where artisanal-scale gold mining activities have been practiced (Marrugo-Negrete et al 2018). An important riparian region that serves as a reference to measure the levels of Hg contamination in Colombia is La Mojana, a region located in the north of the country and where three large Colombian rivers converge: Cauca, Magdalena, and San Jorge.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of this study, some important aspects to consider towards the approach of understanding the results are the family environment and socioeconomic status, according to Hackman et al (2010) and Von Stumm and Plomin (2015), family interactions have an important influence on cognitive stimulation, more specifically on the development of skills such as language and executive function, two of the functions mostly associated in the results of our study. In this sense, some of the differences found in their performance could be related to these influential variables, since constant stimulation from the family, interaction with parents, and the development of skills at school may constitute an important protective factor to counteract the deterioration of altered functions, especially in the context of this area that has been characterized as a growing and sensitive source for human exposure (Barreto et al, 2017;Pino et al, 2018;Marrugo-Negrete et al, 2018;Palma-Parra et al, 2019).…”
mentioning
confidence: 99%